Latino Ministry Competency: Understanding the Transcultural Dynamics of the U.S.-Born Latinos - Rodriguez, Albert R. (Anglican theological review, 2025)
Traditional Latino ministry has focused almost exclusively on first-generation immigrant Latinos, overlooking the English-speaking Latinos, who have lived in the United States for generations. Their English preference and other cultural differences have limited their engagement with traditional Latino congregations. Anglo congregations, who feel called to this English-based Latino ministry, will have the major role in providing a welcoming worship choice to this acculturated Latino constituency. Therefore, a new ministry approach and training are necessary to reach these Latinos who function within a ?Latinized,? transcultural hybridity. Understanding this unique acculturation characteristic is essential to building an effective new paradigm of Latino evangelization that will run parallel to the traditional Latino ministry, each serving two different worshiping constituencies. Also necessary is competency awareness for bishops and diocesan staffs in key U.S. regions who are willing to oversee this new Latino evangelization ministry where Latine communities are concentrated.